Total syntheses of schulzeines B and C - Gurjar, Mukund K.; Pramanik, Chinmoy; Bhattasali, Debabrata; Ramana, Chepuri V.; Mohapatra, Debendra K. (Journal of Organic Chemistry, 2007)
Schulzeines B (2) and C (3) were synthesized by a convergent strategy using epimeric tricyclic lactam building blocks, 4 and 5, and the C28 fatty acid side chain 6. Syntheses of tricyclic lactams (4/5) were achieved by Bischler-Napieralski reaction. Sharpless asymmetric dihy-droxylation and BINAL-H-mediated asymmetric reduction of an enone was employed to prepare the key fatty acid side chain 6. The spectral as well as analytical data of 2 and 3 were in good agreement with the reported data for the natural products, thus confirming their assigned structures.
Keywords: Alpha-Glucosidase Inhibitors; Asymmetric Dihydroxylation; Adjuvant Activity; Pinellic Acid; Ketones; Reduction; Reagents; Configuration; Imbricatine; Alkaloids

First asymmetric total synthesis of penarolide sulfate A(1) - Mohapatra, Debendra K.; Bhattasali, Debabrata; Gujar, Mukund K.; Khan, Mohammad Islam; Shashidhara, K. S. (European Journal of Organic Chemistry, 2008)
Penarolide sulfate A(1), with three contiguous stereogenic centers on a macrocyclic skeleton, affords promise as an alpha-glucosidase inhibitor. Herein, we describe the first asymmetric total synthesis of this natural product. A stereoselective strategy for rapid assembly of the complete framework of the 30-membered macrocyclic core is delineated herein. Sequential amidation and intramolecular Sonogashira cross-coupling reactions were pivotal to the success of our efforts. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: Asymmetric synthesis; C-C coupling; Dihydroxylation; epoxidation; Macrocycles; Regioselectivity; Total synthesis